Categorising on-site problems: A supply chain management perspective on construction projects. Issue 1 (3rd January 2017) - Thunberg, Micael; Rudberg, Martin; Karrbom Gustavsson, Tina
Abstract : Purpose: This study aims to identify and categorise common on-site problems from a supply chain management (SCM) perspective and to trace the origin of these problems in the construction project process, the supply chain or in the intersection between these processes. This allows for identification of how on-site problems affect SCM in construction projects and how they can be mitigated. Design/methodology/approach: A literature review in combination with semi-structured interviews was used to identify on-site problems. This enabled triangulation and strengthened both construct validity and internal validity. Findings: On-site problems can be categorised in one of the four following categories: material flows, internal communication, external communication or complexity. The first category has its origin in the supply chain, the second in the construction project process, the third in the supply chain-construction process intersection on site and the fourth in the construction project as a whole. The findings conclude that on-site problems often originate from construction companies' lack of supply chain orientation. Research limitations/implications: It is suggested that supply chain planning (SCP) can facilitate on-site problem mitigation in construction project management. This extends the body of knowledge of SCP in construction project management and supports the development of effective on-site construction project management. Practical implications: The results show that SCP can aid construction project management in handling on-site problems earlier in the project process. Originality/value: The main value lies in extending the body of knowledge in construction project management research by applying an SCM perspective and by introducing SCP to support more effective construction project management.